Tidal flood and slow onset mobility in the urban community on The Northeast Coast of Central Java, Indonesia - Saptaningtyas Haryani; Nugroho Singgih; Waskitojati Damar; Adi Agung Waskito; Wuryaningsih Cicilia Dwi; Istiyani Ambar; Bacomo Louie; Soreaga Rowena (BIO Web of Conferences)
This paper analyzed the various mobility patterns related to climate change in urban areas, focusing on the impacts of tidal floods and land subsidence in the coastal area of Central Java. The gradual changes in the coastal area are driven by climate change and development plans around the village, which have increased vulnerability. The community often experiences the impacts of rising sea levels and land surface subsidence, damaging the residential environment, public facilities, and hindering transportation and economic activities. This paper explores the experiences of different mobility types, including displacement, voluntary mobility, and immobility. A mixed-method approach was used, involving household surveys, key informant interviews, and community mapping, emphasizing a participatory approach to leverage research for advocacy. The findings suggest that mobility was driven by both the urbanization process and climate change, which have significantly impacted the community. There are various factors influencing their decision to stay or leave the land. Community resilience is one of the drivers of immobility, while the adaptive capacity for livelihood transformation becomes a key factor in their struggle to adapt to climate change impacts.